Penerapan Project Based Learning (PBL) dengan Media Blog Pembelajaran Kimia untuk Meningkatkan Keaktifan dan Hasil Belajar Materi Redoks pada Peserta Didik Kelas X MIPA SMA Negeri 1 Kedungwuni Kabupaten Pekalongan Semester 2 Tahun Pelajaran 2014/2015 - Farwah, Ummu (LP3 Universitas Negeri Semarang, 2015)
The outline of this research issues are how the learning process, how much the liveliness and the result of learning chemistry improve through the application of PBL as media blog for chemistry’s studies. This research are carry out in two cycles, there are 3 meetings in cycle 1 and in cycle 2 there are 2 meetings. The subject of this research are students of class X MIPA 2 of SMAN 1 Kedungwuni Pekalongan semester 2 school year 2014/2015. There is improvement on average grades in periodical test from 71, 08 to 80, 94 and classical completeness increase from 55% to 85, 29%.